2011
DOI: 10.1016/j.bpj.2011.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Mechanophysical Stimulations of Mucin Secretion in Cultures of Nasal Epithelial Cells

Abstract: Nasal epithelial cells secret mucins and are exposed in vivo to airflow-induced mechanophysical stresses, including wall shear stress (WSS), temperature, and humidity. In this work, human nasal epithelial cells cultured under air-liquid interface conditions were subjected to fields of airflow-induced oscillatory WSS at different temperature and humidity conditions. Changes in mucin secretion due to WSS were measured and the role of the cytoskeleton in mucin secretion was explored. Mucin secretion significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 61 publications
2
2
0
Order By: Relevance
“…A similar outcome of denser and more stabilized microtubules in the cell cytoplasm and around the cell nucleus was also observed in endothelial cells exposed to steady WSS of 15–20 dyne/cm 2 for 24 hours exhibited [22], [36], [37]. It is noteworthy that steady WSS applied on nasal epithelial cells induced microtubules fragmentation, while oscillatory WSS resulted in a more organized and filamentous microtubules network in the cytoplasm, including the generation of new microtubules [17], [25]. In another study, metastatic esophageal cancer cells that were exposed to venous shear rate of 200 for 30 minutes showed rapid polymerization and trans-location of tubulin to the leading edge of the cell opposed to cortical ring localization under static conditions [12].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A similar outcome of denser and more stabilized microtubules in the cell cytoplasm and around the cell nucleus was also observed in endothelial cells exposed to steady WSS of 15–20 dyne/cm 2 for 24 hours exhibited [22], [36], [37]. It is noteworthy that steady WSS applied on nasal epithelial cells induced microtubules fragmentation, while oscillatory WSS resulted in a more organized and filamentous microtubules network in the cytoplasm, including the generation of new microtubules [17], [25]. In another study, metastatic esophageal cancer cells that were exposed to venous shear rate of 200 for 30 minutes showed rapid polymerization and trans-location of tubulin to the leading edge of the cell opposed to cortical ring localization under static conditions [12].…”
Section: Discussionsupporting
confidence: 56%
“…It should be noted that elongation of the cells was reported to occur after much shorter exposure time to shear stress [13], [23]. The abovementioned shape change response of endothelial cells to WSS (i.e., elongation and orientation in the flow direction) was assumed cell-specific, since it was not observed in smooth muscle cells and nasal epithelial cells [25], [26], [27]. The present outcome may also be related to the elasticity of the amniotic mambrene on which the EOC cells were cultured.…”
Section: Discussionmentioning
confidence: 99%
“…With additional cultivation on the chip, the cell density decreased slightly in each case, but cilia formation could be still promoted. These results are in accordance with the literature, where the increase in mucin secretion was around 30-80%, as obtained with primary human nasal epithelial cells, after a WSS of 0.05 Pa and 0.5 Pa respectively, for a time period of 5 min, as was previously described in [45]. Furthermore, the influence of mechanophysical stimulation on mucus secretion was reported to be affected more strongly by the time length of WSS than by the level of WSS [46].…”
Section: Formation Of Ciliasupporting
confidence: 93%
“…described in [45]. Furthermore, the influence of mechanophysical stimulation on mucus secretion was reported to be affected more strongly by the time length of WSS than by the level of WSS [46].…”
Section: Mucus Productionmentioning
confidence: 99%
“…An enhanced permeation performance of aerosolized NPs was observed when a 15 L/min airflow was applied (Figure ). The respiratory airflow, in both static and oscillatory patterns, exposes the nasal epithelium to wall shear stresses which have been shown to cause significant yet temporary structural and functional alterations of the ALI-human nasal epithelium. , It was reported that the main response to such stresses is an increase in epithelial cell mucus secretion (mucins and water) and, hence, a decrease in the transport rate across the mucosa and a simultaneous increase in NP accumulation on/within the cell layer may be expected. This impact, however, was subject to the duration of the stress stimulus, which was >15 min, rather than the magnitude of the wall shear stress .…”
Section: Discussionmentioning
confidence: 99%